Studies on expression of sex differentiation program in Momordica charantia L. - WANG Qiao-mei; ZENG Guang-wen (浙江大学学报. 农业与生命科学版)
The sex differentiation process of Momordica charantia first underwent a hermaphroditic stage, then developed forward maleness or femaleness. The soluble protein profile of flower buds at hermaphroditic stage and three early typical development stages of male and female flowers were analyzed with capillary electrophoresis. The result suggested that a 11 kD protein, which existed in all the three development stages of the female flowers with little change of content, might be an “essential protein” for the expression of female flower differentiation program. Similarly, a 30 kD protein might be an “essential protein” for the expression of male flower differentiation program. In addition, the sex differentiation of hermaphroditic flower buds in vitro was inhibited by cycloheximide—an inhibitor of protein synthesis, but not by cordycepin-a nucleic acid synthesis inhibitor.